Initial treatment of Pseudomonas aeruginosa contact lens-associated keratitis with topical chloramphenicol, and effect on outcome. Issue 4 (23rd January 2013) - Bourkiza, Rabia; Kaye, Stephen; Bunce, Catey; Shankar, Jayendra; Neal, Timothy; Tuft, Stephen
Abstract : Aim: To determine whether initial empiric treatment of cases with Pseudomonas aeruginosa contact lens-associated keratitis (CLAK) with chloramphenicol had an adverse effect on outcome. Methods: We retrospectively reviewed 139 cases of culture-proven P. aeruginosa CLAK seen between 2007 and 2009. We recorded chloramphenicol use prior to the prescription of a fluoroquinolone, the visual acuity (VA) when the fluoroquinolone was started and at final follow-up, complications and duration of follow-up. Results: 46 patients (33.1%) had used chloramphenicol before they were prescribed a fluoroquinolone. When we compared this group with patients who had initial treatment with a fluoroquinolone, the ulcer size was larger when a fluoroquinolone was started (Mann–Whitney, p=0.018). Although the initial VA was also worse in the chloramphenicol group (p=0.02), and complications more frequent (p=0.016), the final VA in both groups was similar (p=0.29). The chloramphenicol group had a longer median follow-up of 37 days (IQR: 9–310 days) compared with 21 days (IQR: 6–80 days) for the non-chloramphenicol group (p=0.09). Conclusions: Chloramphenicol 0.5% eye drops are available in the UK without prescription. Chloramphenicol had been used in one-third of cases of P. aeruginosa CLAK prior to the use of a broad-spectrum antimicrobial, which was associated with more complications and a longer interval to resolution, but with no adverse effect on final VA.